(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The components of the pension system of Ukraine after the reform are anylyzed in the article. The essence of each of the three levels of the pension system is described. The sources of costs formation of the Pension Fund of Ukraine as the main subject of the solidarity system of the obligatory for all state pension insurance are pointed out. A dynamics of the main indicators of the budget of the Pension Fund of Ukraine in 2010‒2015 is adduced. In the article it is noted that the deficit of the Pension Fund of Ukraine is the result of the demographic crisis in the country. The demographic crisis means continuous deterioration of the age structure of the population and unfavorable, in terms of formation of the pension funds, changing of the indicators of the demographic loading. This trend is typical for most countries of the world. The correlation of the number of workers to the number of retirees in developed countries, the expected lifetime in Ukraine and some developed countries are shown in the article. The analysis of the activity of the major financial institutions that provide services in the sphere of the private pension provision, namely private pension funds, insurance organizations and banking institutions are carried out.